Efektivitas Model Guided Inquiry terhadap Higher Order Thinking Skills: Systematic Review Pembelajaran Sains Indonesia - Tarigan, Calvin Mahaga; Gultom, Esmeralda; Harisi, Fitria Fadila; Simanjuntak, Mariati Purnama (Universitas Pendidikan Mandalika, 2025)
The Guided Inquiry (GI) model has been extensively applied in science education to foster Higher Order Thinking Skills (HOTS), yet systematic evidence of its effectiveness across educational levels in Indonesia remains limited. This study conducted a narrative systematic literature review (SLR) of 20 studies (11 experimental/quasi-experimental, 4 meta-analyses, and 5 systematic reviews) published between 2019 and 2025, aiming to evaluate the effectiveness of GI in improving HOTS—critical thinking, creative thinking, and problem solving—as well as Science Process Skills (SPS) in Indonesian elementary, junior high, and senior high school science contexts. The review followed PRISMA guidelines and involved database searches in Portal Garuda, SINTA, Google Scholar, Scopus, ERIC, and Web of Science, using relevant keywords. Inclusion criteria required studies to focus on GI in science learning, report HOTS or SPS outcomes, and be published in reputable Indonesian or international journals. Study quality was assessed using adapted JBI Critical Appraisal Tools. Meta-analytic findings revealed very large effect sizes for critical thinking (g = 1.33), creative thinking (g = 1.10), and problem solving (g = 1.31), while experimental studies showed high-category SPS gains (N-Gain = 0.7) and improved scientific literacy. GI effectiveness was consistently high at the junior and senior high school levels (effect size 0.8–1.3), but varied at the elementary level (0.4–1.10), depending on scaffolding intensity and implementation duration. Integration with technology and STEM contexts led to superior outcomes. The review concludes that GI is highly effective in enhancing HOTS and SPS across levels, though effectiveness depends on adaptive scaffolding and learning conditions. Limitations include study heterogeneity and potential publication bias.